Supramolecular Fixation of Magnesium Tetraphenylporphyrin with Ethanolamine for SO2 Removal - Cheng1, Jingshun; Zhang2, Jianbin; Huo2, Tianrui; Gao2, Fei; Zhang2, Yongfeng (Asian Journal of Chemistry, 2013)
In this work, supramolecular fixation of magnesium tetraphenylporphyrin (MgTPP) with ethanolamine for removal of SO2 was investigated in CH2Cl2 by steady-state fluorescence and UV-visible spectroscopic techniques. The UV-visible spectra showed that the interaction of MgTPP with ethanolamine resulted in red shift of 2 nm for MgTPP Soret absorption band. Once introduced, SO2 competes with MgTPP for ethanolamine, which eventually leads to the release of MgTPP. The fluorescence spectra suggested that MgTPP interacted with ethanolamine to form 1:1 molecular adducts and showed that the binding of MgTPP with ethanolamine with the association constants (Kassoc) of (0.584-0.784) is not only endothermic but enthalpy-driven with DH = 14.852 kJ mol-1, DS =45.290 J mol-1 K-1 and DG = 1.333 kJ mol-1 at T = 298.15 K.